A Study of Management Behavior by Use of Competitive Business Games - Symonds, Gifford H. (Management Science, 1964)
A general model has been developed for a class of business games to represent the activities of individual firms in a hypothetical oligopolistic industry. Although hypothetical, the games allow the players to transfer mentally to the real business world. The players who act as competitors build and operate their individual plants with specified technology to produce a single homogeneous product. The product is sold competitively to households, and labor supplied by the households is employed in the industry through competitive bidding of the competitors. Thus, there are two competitive markets established, with the firms competing for a limited supply of labor on the one hand, and competing for a limited sales fund on the other hand. Managerial decisions for each firm include labor employment offerings and wage rate, product sales offerings and product prices, production and inventory, plant expansion, money borrowing, sales credit, and dividends paid to stockholders. In some cases there is a market for “efficiency units” used to improve technology. The competitors may select wage rates and product prices freely, since there are no internal relationships in the model. Aggressive competition for labor results in increasing wage rates and aggressive competition for the sales fund results in low product profit. Various regulations are introduced concerning monopoly, taxation, credit, and bankruptcy. The general results of this study show that managerial behavior in an oligopoly exhibits varying strength of agressive competition producing the usual business cycle, and further that competitors will act to “stabilize” the industry by self-regulation of speculative activities. An examination of the technological input to these business games shows that competitors will invest funds to improve efficiency only when their marginal utility of money is well below that represented by the fixed interest rate.